JOHN MASTERS – A VOICE FROM THE COLONIAL PERIPHERY - Fryska, Ewa (European Scientific Journal, ESJ, 2013)
This article discusses three novels by John Masters (1914 - 1983), an ardent advocate of the British Empire. Through the characters and situations he creates, the author promotes the idea of British imperial commercialism. Masters experienced a typical life of a fifth generation English settler in India: having spent only a short period in England, the ruling center, when he was sent to school, he only knew the social and political conditions of the colonized periphery, which turned him into a unique chronicler of the Anglo-Indian history. The novelist uses the history of the East India Company, an institution that helped the Empire to succeed, as the subtext of his novels. As an ardent advocate of the Company’s rule, Masters uses his novels to laud the English, as their presence in India means the improvement of living standards to the local inhabitants. Coromandel! (1955) presents the beginnings of the East India Company in the 17th century. In The Deceivers (1952) Masters shows how the Company developed into a huge administrative institution that had its own army and a wellfunctioning and incorruptible Indian Civil Service. In Nightrunners of Bengal (1951) Rodney Savage is proud that everywhere in India he is surrounded by ‘symbols of the colossal empire of the Honourable East India Company’. Yet, the Indian Mutiny of 1857 ruined the Company’s privileged position and it lost its administrative powers. As Masters is one of the few voices from the colonial periphery, his contribution to modern literature is unique.